Beyond internationalisation and isomorphism – the construction of a global higher education regime. Issue 4 (2nd October 2019) - Zapp, Mike; Ramirez, Francisco O.
ABSTRACT: National higher education systems are undergoing profound changes, discussed in many but unrelated studies as outcomes of internationalisation dynamics and institutional isomorphism pressures. We propose to link these studies by emphasising the influence of both internationalisation and isomorphism on the formation of a global educational regime. Through a broad range of indicators, we describe the growth of the discursive, normative, and regulatory dimensions of such a global higher education regime. We find evidence of the following developments: (1) a rapidly growing network of international organisations focused on conferences, initiatives, and programmes supporting a global higher education agenda; (2) a striking increase in the number of international and national accreditation agencies, their mutual cross-national recognition as well as the number of universities that are nationally and internationally accredited; and lastly, (3) parallel increases in regional qualification frameworks and in the implementation of national qualification frameworks. These developments create integration pressures manifest in the mutual recognition of higher education degrees, for which a new generation of regional conventions has emerged worldwide in the past two decades. We discuss these processes and their implications for understanding 'national' higher education as well as the threats and limits to the burgeoning higher education regime.